Lord Only Knows: Judean Imagination and Cyrus's Relationship with Yhwh - Wilson, Ian Douglas (Die Welt des Orients, 2025)
The book of Isaiah refers to Cyrus the Great as Yhwh's "shepherd". The book presents him as a divinely "anointed" king, chosen to subdue nations and to elevate the Judean deity. How would Judeans of the Persian period (and later) imagine this king and his special relationship with their deity? Would Judeans think that their deity was present in the mind of a Persian king? In other words, would they imagine that Cyrus knew Yhwh? This article argues that Judeans probably did think this way. The ancient Judean discourse on kingship suggests as much. However, for Judeans who read and considered texts like Isaiah, the details of Cyrus's personal knowledge of Yhwh would be less important than the general knowledge that Yhwh was and remains the true king of the world-a truly universal deity-and that Cyrus was employed to that end.